Photocatalytic Degradation of Congo Red Dye using ZnFe2O4/SnO2 Composite with Response Surface Methodology (RSM) Optimization - Abduh, Gierrald; Said, Muhammad; Hariani, Poedji Loekitowati (Trends in Sciences, 2025)
In this investigation, the synthesized ZnFe2O4/SnO2 composites for the photocatalytic degradation of Congo red dye. Doping SnO₂ onto ZnFe2O4 optimized the energy gap, promoting light absorption in the visible spectrum. The ZnFe2O4/SnO2 composites were analyzed using XRD, UV-DRS, SEM-EDS, VSM, and pHpzc. Photocatalytic degradation is optimized using Central Composite Design (CCD), which is based on response surface methodology (RSM). The XRD characterization results of the ZnFe2O4/SnO2 composites demonstrate the success of the synthesis method. The composite has a combined 2θ of ZnFe2O4 and SnO2, with a crystallite size of 17.50 nm. A band gap value of 2.46 eV indicates that the material can absorb most of the visible light spectrum. The EDS mapping results verify the presence of SnO2 on the surface of ZnFe2O4, and the saturation magnetization value of 12.80 emu/g confirmed the composite’s magnetic properties. Degradation optimization using RSM indicated that the quadratic model effectively characterizes the photocatalytic degradation of Congo red dye. The RSM model’s high accuracy in predicting experimental outcomes is evidenced by the minor difference in efficiency degradation between experimental and predicted values, with an R2 of 0.9851 and a p-value < 0.05. The optimum degradation efficiency was achieved at a solution pH of 4, a Congo red dye concentration of 10 mg/L, and an irradiation time of 80 min. The composite exhibits great stability, efficiency, and reliability; the reuse evaluation after 5 cycles indicated a deterioration reduction of less than 5 %. HIGHLIGHTS Doping SnO₂ into ZnFe₂O₄ reduces the band gap energy, thereby enhancing its absorption capability within the visible light spectrum. Degradation optimization using RSM indicated that the quadratic model where solution pH, dye concentration and irradiation time affect degradation efficiency. The ZnFe₂O₄/SnO₂ composite demonstrated the ability to degrade over 90% of Congo red dye The deterioration efficiency diminished by less than 5% after after five consecutive cycles, signifying exceptional material stability. GRAPHICAL ABSTRACT